Why IoT Enablement of Agrifood Transportation Disappoints Its Stakeholders: Unravelling Barriers for Enhanced Logistics - Deepika Joshi; Sumit Gupta; Amit Vishwakarma; Sandeep Jagtap (Journal of Food Quality)
The present research work investigates the barriers of weak IoT adoption in agrifood transportation, with special reference to India. It is built on a premise that few barriers upshots from the other more impactful ones. Thus, it is important to identify their linkages and classify them based on their strength of relationship. The data collected from 13 agricultural technology (AgriTech) firms of India were subjected to integrated techniques of M-TISM and Fuzzy MICMAC. As a result, a unique position of autonomous, dependent, linkage, and independent barriers was obtained which revealed that inadequate Internet connectivity, interoperability, and unclear roadmaps are precarious to the use of IoT in agrifood transportation. They are responsible for creating issues like data processing, vehicle tracking, and data privacy. This study offers a contextual phenomenon of barriers that may assist AgriTech stakeholders in developing appropriate strategies to embrace IoT transformation. It extends the theoretical literature by providing critical connections that aspiring researchers can examine through hypothesis testing or building a hierarchical framework. A sensitivity analysis is suggested to optimise decision-making and bring out a robust and reliable set of obstacles.